Conflict of Norms in the Brazilian Bankruptcy Law - Tortelli, Carlos; Mallmann F. A. Brandão, Larissa (International Journal of Insolvency Law, 2018)
[extract] In 2005, Brazil implemented a new Bankruptcy Law (Law No. 11.101, dated February 9, 2005), modeled largely after the Title 11 of the United States Code, also known as the United States Bankruptcy Code. The current Brazilian system provides three alternatives for insolvent legal entities: (i) judicial reorganization, a court-supervised reorganization proceeding; (ii) bankruptcy, a court-supervised liquidation proceeding; and (iii) extrajudicial reorganization, an out-of-court reorganization proceeding. The possibility of recovery of an activity momentarily in crisis, with the possibility of implementing a corporate restructuring plan, renegotiation of liabilities with creditors and business continuity was undoubtedly the innovative point of the Law. Unfortunately, the Brazilian Bankruptcy Law embodies within itself serious contradictions – legal antinomies – which prevent the fulfillment of the objective of the Law. One of the most serious antinomies is the conflict between Article 47 and Article 49, Paragraph 3. This antinomy has the potential to impair the judicial recovery of the economically viable company. For this reason, this antinomy must be widely discussed, as well as the cause and the nature of this conflict of norms.